Peningkatan Hasil Belajar Siswa pada Materi Energi Gerakan melalui Model Contextual Teaching and Learning (CTL) pada Siswa Sekolah Dasar - Sri Martini (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
This study aims to improve the result study of sains through CTL. This research is a Classroom Action Research. The subject of the research is the 3th grade student at Ngabenrejo 3 Elementery School. The research instruments are observation sheets, pretest and postest. Data analysis was done by descriptive statistc technique by determining mean, median, mode, lowest score, highest score, and completeness of study individually or classically presented in percentage form. The result of this research shows that CTL can increase the result study of sains of the 3th grade student. This can be seen from the increase of the pra cycle stage which shows the result study of sains of the students by 40, 09 % with the average score is 57, 04 has increase in the first cycle of 68, 18 % with the average score is 70 and the second cycle there is also a significant increase of 95, 45 % with the average score is 85, 68. This means that the implementation of class action research is successful. Based on the result of the research, the implications that can be given, among others, is this study provides an overview of the improvement of the result study of student after applying the CTL. This learning provides students the opportunity to learn independently and improve their creativity